Detection Of Primary Sites In Cerviacal Lymph Nodes Metastasis - Akter, Sylvia; Alam, Monsur; Akram, Saleh (Bangladesh Armed Forces Medical Journal, 2026)
Background: Metastatic cervical lymphadenopathy is commonly encountered in adult and elderly population in otolaryngological practice. Ignorance, illiteracy, lack of proper health care education as well as lack of proper orientation of the clinicians regarding management of mitotic neck node have enabled the patients to suffer from morbidity and mortality. Objectives: The purpose of this study was to detect variable primary sites which mostly metastasize to different neck nodes. Methods: This cross-sectional study that was conducted among purposively selected 60 patients with metastatic cervical lymph node in the Department of Otolaryngology & Head-Neck Surgery of Combined Military Hospital Dhaka from July 2021 to June2022. Data were collected in pre designed data collection sheet by taking history, clinical examination, investigations and surgical treatment. Histopathological (from fine niddle aspiration cytology (FNAC), punch/incisional biopsy or examination under Anesthesia and direct Laryngoscopic biopsy) reports were collected. Result: Lesions in primary site was detected in 88.53% of study population. Out of these 81.13% cases were squamous origin and rest had been originated from non-squamous epithelium. Most common primary site were detected as from larynx. Males were affected more in comparison to female and age of cases were in between 20 years to 90 years. Metastatic lymph nodes were found single sided in 81.67% cases whether both sided were present in 16.67% patients of Ca-larynx. Among the cases single Lymph node involvement was determined in 36.6% & multitudinous in 63.33%. Cervical lymph nodes of level–II involvement were mostly found which was about 40% and then we found level II+I neck nodes involvement about 30%. Conclusion: Early presentation and appropriate modalities should be taken to diagnosed the enlarged neck lymph node for effective intervention/treatment specially older people. Bangladesh Armed Forces Med J Vol 58 No (2) December 2025, pp 50-56